Positive and Negative Selection in Bargaining: An Experiment - Dongkyu Chang; Duk Gyoo Kim; Wooyoung Lim (Center for Economic Studies and ifo Institute (CESifo), 2022)
We consider infinite-horizon bargaining in which an uninformed seller sequentially makes a price offer to a privately informed buyer who decides whether to accept or reject it in every bargaining round. Existing theories suggest that the presence (absence) of an arbitrarily small outside option available to the buyer in this dynamic screening problem leads the seller (buyer) to enjoy a substantial surplus, and we examine the validity of the differences in the share of the surplus theoretically and experimentally. We first show that the theoretical differences collapse if an arbitrarily small fraction of optimistic buyers would believe that the sellers sometimes ask for a lower price in the subsequent rounds. We then present experimental evidence that the earnings of both the buyers and the sellers when the buyer has an outside option are not significantly different from those without the outside option. We find supporting evidence that some buyers reject the current-round offers, optimistically believing that the next offer would be more favorable to them.
Keywords: C78; C91; D03; 330; positive selection; outside options; laboratory experiments